1625. Real-World Outpatient Utilization of Ceftolozane/Tazobactam in Physician Office Infusion Centers (OICs). (31st December 2020) - Van Anglen, Lucinda J; Nathan, Ramesh V; Nathan, Ramesh V; Metzger, Brian S; Luu, Quyen; Schroeder, Claudia P
Abstract: Background: Ceftolozane/tazobactam (C/T) is indicated for the treatment (tx) of complicated Gram-negative infections including urinary tract infection (cUTI), intra-abdominal infection (cIAI), and hospital-acquired/ventilator-associated bacterial pneumonias caused by susceptible bacteria. Real-world data on the use of C/T are limited. We present a multicenter observational review of C/T outpatient utilization in Infectious Disease OICs. Methods: Medical records of patients (pts) who received C/T for ≥3 doses from May 2015 to Sept 2019 were reviewed. Data included demographics, diagnosis, disease history, pathogens, C/T tx hospitalizations, emergency department (ED) visits and clinical outcomes. Clinical success was defined as complete or partial symptom resolution at completion of C/T with oral antibiotics as needed. Persistent infection and early discontinuation (D/C) of C/T were deemed non-successful. Indeterminant outcomes were deemed non-evaluable. Chi Square, Fisher's exact, and t-tests were used to identify characteristics associated with clinical outcome. Results: 120 pts (mean age: 59±15 years, 60% male) from 33 OICs were identified. Median Charlson score was 5 (IQR, 3-7), with 43% immunocompromised, and 77% refractory/recurrent disease. Primary infections were bone and joint (25%), cUTI, (24%), respiratory tract (18%), cIAI (18%), complicated skin and skin-structure (12%), and bacteremia/endocarditis (3%). Most pts had multi-drug resistant Gram-negative pathogens (80/108; 74%), predominantly Pseudomonas aeruginosa . Polymicrobial infections were reported in 44%. Median duration of C/T therapy was 21 days (IQR, 14-34). C/T was initiated in the OIC in 59% of pts. Overall clinical success was 86% (100/117), with rates by infection type in Fig 1. Non-success was reported in 17, 10 due to persistent infection and 7 due to adverse events. The adverse events led to early D/C of C/T, all with resolution. Statistically, infection type did not impact success rate. Hospitalizations and ED visits during tx occurred in 5% of pts with successful outcomes and 35% of pts with non-successful outcomes (p < 0.001). Fig 1. Clinical success rates of C/T by infection type Conclusion: These real-world results support the effectiveness of C/T in a wide variety of complicated Gram-negative infections treated in the outpatient setting. Disclosures: Lucinda J. Van Anglen, PharmD, Merck & Co. (Grant/Research Support) Ramesh V. Nathan, MD, FIDSA, Merck & Co. (Other Financial or Material Support, Grant Steering Committee Member) Brian S. Metzger, MD, MPH, Allergan (Speaker's Bureau)Cumberland (Speaker's Bureau)Melinta (Speaker's Bureau)